Comparison of Early Mortality and Morbidity of Off Pump vs On Pump Coronary Artery Bypass Graft Surgery in High-Risk Patients - Nawaz, Atif; Ali , Nasir; Hayat, Sikandar; Sobia, Farah; Sajjad, Ahsan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the early mortality and morbidity of high-risk patients following off-pump and on-pump Coronary Artery Bypass Grafting (CABG).Study Design: Analytical Cross-sectional study.Place and Duration of Study: Tertiary Care Cardiac Center, Rawalpindi Pakistan, from Oct 2022 to Mar 2023.Methodology: Two hundred and forty-three patients undergoing on-pump CABG(ONCAB) or off-pump CABG(OPCAB) with an Ejection Fraction (EF) of